Transient Neonatal Diabetes Mellitus in a Very Preterm Infant due to ABCC8 Mutation - Barbara Piccini; Caterina Coviello; Livia Drovandi; Artuso Rosangela; Francesca Monzali; Emilio Casalini; Sabrina Giglio; Sonia Toni; Carlo Dani (Thieme Medical Publishers, Inc., 2018)
Neonatal diabetes mellitus (NDM) is a monogenic form of diabetes occurring within 6 months from birth. NDM can be permanent or transient (TNDM). We report the case of a preterm infant with TNDM due to an ABCC8 mutation identified by next-generation sequencing. The pancreatic adenosine triphosphate (ATP)-sensitive K+ (K-ATP) channel is a key regulator of insulin secretion. Gain-of-function mutations in the genes encoding the Kir6.2 (KCNJ11) and SUR1 (ABCC8) subunits of the channel cause neonatal diabetes. The patient was successfully managed with insulin lispro at a 1:100 dilution, drawn up in an insulin pen injector with a 4-mm needle. The insulin lispro dilution allowed administration of the exact insulin doses, obtaining a good glycemic control and minimizing the burden of injections. At 2 months, corrected age insulin doses were progressively decreased until discontinuation.